Conjugated type A trichothecenes in oat-based products: Occurrence data and estimation of the related risk. (January 2023) - Prusova, Nela; Behner, Adam; Dzuman, Zbynek; Hajslova, Jana; Stranska, Milena
Abstract: Currently, increasing attention is being paid to conjugated mycotoxins in plant-based foods because of their assumed bioavailability and health risks. However, analytical standards for most mycotoxin glycosides are not available and risk assessment processes have not yet been completed because of the lack of occurrence data. Our study presents a method for efficient pre-concentration of type A trichothecene glycosides using immunoaffinity columns, followed by indirect determination after enzymatic hydrolysis. This method was applied to 52 various oat-based products. Analytical determinations of both free and glycosylated mycotoxins were performed by ultra-high performance liquid chromatography coupled with high-resolution mass spectrometry. Free T-2 toxin and T-2-monoglucosides were present in 92% and 69% of samples, respectively. Free HT-2 toxin and HT-2-monoglucosides were present in 92% of samples and HT-2-diglucosides were detected in 38% of samples. The percentage of HT-2 present in the form of glycosides was up to 56% of the total HT-2 content. Graphical abstract: Image 1 Highlights: From 52 oat-based products, T-2 and HT-2 were quantified in 92% of samples. In addition to HT-2 and T-2, their mono-/di-glucosides were found in these samples. HT-2 bound in glycosides represented up to 56% of total HT-2 in oat-based products. The highest percentage of HT-2 'masked' in glycosides was in flakes with sprouts. The content of 'masked' HT-2+T-2 in foods is higher than considered by EFSA so far.